POLICY OF CRIMINAL LAW PROTECTION OF THE CONSTITUTIONAL ORDER OF THE MODERN STATE - Vasiljević, Dragana (Politeia, 2023)
The policy of criminal law protection of the constitutional order as a part of the overall social policy has been greatly changed in the modern state. This rational and organized activity is focused on protection of the constitutional order by incriminating certain socially unacceptable behaviors. This is one of the social goals that has always been present, determined by socio-political forces. Although incrimination of certain behaviors, regardless of the immediate object of criminal law protection, indirectly serves the protection of society as a whole, the article emphasizes the features of incriminations that are directly aimed at protecting the constitutional order and political order of the state. This segment of criminal law protection, given the security challenges and threats to which the modern state is subject, has necessarily undergone certain changes. It is about expanding the zone of criminality, that is, the emergence of new incriminations, but also a much different position of the perpetrators of the so-called political criminal offences.